The Practicality of Calligraphy Learning Model - Moh In'ami; Etika Vestia; Ade Setiawan (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
This paper presents the practicality of the calligraphy learning model based on imlaiyyah rules. Imlaiyyah rules need to be mastered by calligraphers, as a means of control so that there are no writing errors in writing verses of the Qur'an. The verses of the Qur'an must be written beautifully visually and grammatically correctly so that every eye that reads it feels comfortable and there are no mistakes in meaning and interpretation. The research method used is the Research & Development (R&D) method. Teachers who teach calligraphy must also find it easy and practical to convey the calligraphy material to be presented. Do not feel burdened, happy to teach it, and can achieve learning targets as desired. The results of this study can be seen from the results of the instructor's response, including the range of very positive qualifications with very practical criteria.